Fragile privileges: autoimmunity in brain and eye - Wekerle Hartmut; Sun De-ming (Acta Pharmacologica Sinica, 2016)
Brain and eye tissues are subject to a reduced version of immune surveillance, which has evolved to protect the particularly sensitive tissues from accidental bystander damage created by regular inflammatory responses. Yet, there are autoimmune diseases in both organs. This review discusses the nature of immune reactivity in the healthy eye and brain tissues, and mechanisms that can overcome the protective barriers to create tissue specific disease.